Development of Reporting Guidelines for Systematic Review for Environmental Epidemiology Studies - Lee, Kyung Joo (Université d'Ottawa / University of Ottawa, 2021)
Systematic review is a type of review that identifies, assesses, and combines all the published empirical evidence on a specific topic by using explicit, systematic methods. This type of reviews often includes a meta-analysis, a statistical tool used to combine the collected data into a quantitative summary estimate. Guidance documents such as the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) were developed to improve the reporting of systematic reviews of randomized controlled trials. Systematic reviews are commonly used in the field of healthcare research and are increasingly being employed in the field of environmental epidemiology. Environmental epidemiology studies examine exposures in populations and their associations with health outcomes. This field contains several unique considerations that require a careful and critical assessment to ensure the validity of results and to make the data or information more useful for the readers. However, to our knowledge, there is currently no guidance document for conducting systematic reviews that comprehensively addresses the specific issues in this field. Therefore, the objectives of this proposal are twofold: (1) to conduct a systematic review of the currently published epidemiology systematic reviews on a specific topic (mercury exposure and children autism spectrum disorder) to identify analytical issues encountered, and (2) use the experience and other potential solution identified in the literature to develop a guidance or recommendation document for conducting systematic reviews of environmental epidemiology studies. Akin to reporting guidelines for randomized controlled trials, a reporting guideline for environmental epidemiology is anticipated to increase the clarity and transparency of publications and enhance the usefulness of systematic reviews for knowledge synthesis.
Keywords: Systematic review; Meta-analysis; Environmental epidemiology; Reporting guidelines; Autism spectrum disorder; ASD; Mercury; Methylmercury